2022
DOI: 10.1007/s00431-022-04610-9
|View full text |Cite
|
Sign up to set email alerts
|

Change in physical fitness due to the COVID-19 pandemic lockdown in French adolescents: a comparison between two independent large samples from Diagnoform battery

Abstract: Numerous studies reported a significant decline in physical activity level in adolescents as a result of the COVID-19 lockdown. Physical fitness is recognized as a powerful marker of health in youth. The aim of this study was to evaluate the impact of the COVID-19 pandemic lockdown on health-related physical fitness in French adolescents. Two cross-sectional studies were performed comparing two different groups of French adolescents, before (sample 1) and after the first lockdown (sample 2). A total of 1231 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…To our knowledge, there are currently only a few studies that analysed physical fitness changes among children both during and after COVID-19 restrictions. 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 These studies agree that cardiorespiratory fitness, 26 , 27 , 28 , 29 , 30 , 32 , 33 , 35 lower body explosive power, 27 , 28 , 33 , 35 and speed decreased, 28 , 32 after COVID-19 containment restrictions, while more generally, a lower share of participants was meeting the recommended physical fitness levels. 29 , 33 , 35 Conflicting evidence was reported regarding other components of muscular fitness.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…To our knowledge, there are currently only a few studies that analysed physical fitness changes among children both during and after COVID-19 restrictions. 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 These studies agree that cardiorespiratory fitness, 26 , 27 , 28 , 29 , 30 , 32 , 33 , 35 lower body explosive power, 27 , 28 , 33 , 35 and speed decreased, 28 , 32 after COVID-19 containment restrictions, while more generally, a lower share of participants was meeting the recommended physical fitness levels. 29 , 33 , 35 Conflicting evidence was reported regarding other components of muscular fitness.…”
Section: Introductionmentioning
confidence: 60%
“…Numerous studies have analysed the effects of COVID-19 restrictions on physical fitness, although most focused on immediate effects. These studies included children and adolescents of different ages (7–18 years old) and covered various geographical regions across the globe, i.e., Austria, 27 China, 32 England, 26 France, 28 , 33 Germany, 34 , 45 Portugal, 30 Singapore, 31 South Korea, 35 and Spain, 29 indicating a global representation of research on the impacts of COVID-19 restrictions on physical fitness. Sex distribution was also considered in some studies, 27 , 28 , 29 , 32 , 34 , 35 with findings suggesting potential sex-based differences in physical fitness outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results in relation to muscle function in the literature are scarce and only refer to the standing broad jump, which showed mixed results. Basterfield et al 13 reported an increase in the standing broad jump performance (6.8 ± 13.1 cm), while Chambonnière et al 19 and Béghin et al 21 showed a decrease around 34.6 and 23.3 cm respectively. The present results reflected a downward trend in performance that did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 94%
“…Diabetes care teams should encourage patients to stay physically active and should counsel them regarding their eating behavior and their screen time habits. This may-however-not be sufficient to counteract the increase in sedentary behavior; more systematic programs fostering physical activity in children's and adolescents' daily life may be necessary [35][36][37][38]. In this study, we compared BMI during the pandemic with the year 2019, and therefore, longer-term pre-pandemic trends in weight gain cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%